(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In developed countries of the world, the activity of small business and private entrepreneurship is rapidly developing as a strategic task of economic policy. "Small business and private entrepreneurship account for 55-67% of the gross domestic product of developed countries. This indicator is 52-55% in the USA, 52-57% in Japan, and 63-67% in the European Union. In Western European countries, out of 17.1 million enterprises operating in the private sector, 90.9 percent are small business enterprises. They account for 50 percent of the total industrial volume, 67 percent of the service sector, and almost 90 percent of construction and trade. However, small businesses and private entrepreneurship account for about 30-40% of exports from developed countries. This figure is 30% in the USA, 27% in EU countries, and 15% in Japan.